Effectiveness of Talcum Powder for Decipherment of Latent Fingerprints on Various Substrates - Nigam, Kriti; Das, Tanurup; Harshey, Abhimanyu; Kumar, Akash; Kapoor, Neeti; K Yadav, Vijay; Srivastava, Ankit (Asian Journal of Chemistry, 2020)
Decipherment of latent fingerprints are one of the most common tasks in crime scene investigation as it carries the unique identification feature of the individuals related to that offence. Powder dusting is the most suitable method to develop latent prints on a wide range of nonporous and semiporous surfaces. In present work, a commercially available talcum powder, generally used as a common cosmetic product, has been used to decipher latent prints on 28 non-porous and semi-porous surfaces commonly encountered in daily life. The powder is economic and harmless in nature and easily available in market. The results showed that the powder developed good quality fingerprints on most of the surfaces and can be a good substitute of conventional powders.